Optimal controller design for A 2-AXLE railway vehicle suspension system [electronic resource] - Siti Durrani Mohd Dom Arang Bilong, 1983-; Fakulti Kejuruteraan Elektrik (2010)
Thesis (Sarjana) - Universiti Teknologi Malaysia, 2010